PERANCANGAN SISTEM INFORMASI PENCATATAN KEHADIRAN MAHASISWA DENGAN TEKNOLOGI QR CODE - Ferdinand Lanvino; Andre Yonathan Sukhoco; Wilianti Aliman; Suryanto (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
QR Code use in society has been growing lately. The trend provides ideas for applying it to the system in higher education. The use of smartcards to record student attendance, which has been available for a long time at the STMIK LIKMI campus, needs improvement which is not too dependent on hardware such as card readers. The purpose of this research is to develop an attendance recording information system using QR Code technology. The development of the QR Code-based student attendance recording system was carried out using a prototyping model and object-oriented approach. Unified Modeling Language (UML) diagrams are used to help model the system. The implementation process on the server side and client side is carried out after going through the analysis and planning process. On the server side, a web service system is developed that functions to provide data or resources to the client. On the client side, a desktop application is developed which will be installed in the classroom to display the QR Code and a mobile application that will be used by two types of users, namely lecturers and students. Applications in the attendance recording system are then tested using the blackbox method. This research resulted in an attendance recording information system that includes a desktop application and a mobile application. Mobile application users can record their attendance by simply scanning the QR Code provided in accordance with the relevant lecture sessions. Both application platforms can be integrated by implementing a web service through internet connection.